Scaly trade: Analyses of the media reports of pangolin (Pholidota) scale interceptions within and out of Africa - Zwannda Nethavhani; Catherine Maria Dzerefos; Raymond Jansen (Global Ecology and Conservation, 2025)
Despite the international trade ban (CITES, Appendix I), African pangolin trade and shipping within and out of Africa persist. Phataginus tricuspis and Smutsia gigantea are now classified as Endangered, and Phataginus tetradactyla and Smutsia temminckii as Vulnerable on the IUCN Red List. To date, the comprehensive trade data of African pangolin scales is still lacking. Here we analyzed pangolin interception data linked to Africa from social media, pangolin organizations, and online news media between 2016 and 2024. We report 130 seizure incidents accounting for 287,272 kg of African pangolin scales involving 15 African and seven Asian countries. Overall, Nigeria and the Democratic Republic of Congo are major exporters, while China, Vietnam, and Singapore are the major importers of African pangolin scales. Domestic interceptions were highest in Nigeria, Cameroon, and Uganda, signifying that they may be transit countries. While there was a negative correlation between the number of seizures and years, and the quantity of scales seized and years, 2019 reported a sharp increase in quantity of scales (97,877 kg; 34 % of the data). Furthermore, both metrics declined after 2019, with interceptions increasingly confined to African countries. This could reflect lack of resources, low capacity for identifying pangolin scales, change in routes of trafficking over time, underground trade, law enforcement and customs corruption. Our study contributes to the growing body of data on the African pangolin trade by focusing on trade routes, seizures, and importer and exporter countries, which are essential for effective conservation management.